PENINGKATAN KEMAMPUAN MEMBACA AL-QUR’AN GURU PADA ERA NEW NORMAL DI SD NEGERI 3 BANDAR AGUNG - Toyib Subagio (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2021)
This article aims to describe the efforts to improve the ability to read the Al-Qur’an teachers in the New Normal Era at SD Negeri 3 Bandar Agung. The data collection methods used were observation, interview and documentation. The results showed that the teacher’s ability to read Al-Qur’an could be improved through the application of the Al-Qur’an learning habit method with peer guidance, the use of in-formal educational institutions and the provision of adequate facilities and infrastructure. The positive contribution of this article can provide information to the wider community about the implementation of strategies to improve reading skills of the Qur’an that are suitable for a teacher.